Peran Hukum dalam Pemberantasan Kemiskinan: Studi terhadap Kebijakan dan Implementasi Program Pemerintah - Pangulu, Diska; Laba, Adrianto; Moonti, Roy Marthen (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of law in poverty eradication in Indonesia through the analysis of regulations and implementation of government programs. With a descriptive qualitative approach based on literature studies, this study explores the effectiveness of books as an instrument of public policy. The findings show that the law has not functioned optimally as a tool for social transformation, tends to be administrative and not yet adaptive to the dynamics of poverty. Case studies in several regions such as Malang, Trenggalek, and Aceh Tamiang highlight weak coordination, data validation, and community participation. The main obstacles include limited local regulations, inaccurate targeting of assistance, and minimal legal-based supervision. Therefore, proactive, participatory, and contextual legal reform is needed so that poverty alleviation policies truly side with vulnerable groups. The law must be present not only as a norm, but as a structural force that guarantees distributive justice and social empowerment.